Competencies for reading and writing the English language present in the students of a a venezuelan university (Research, Society and Development, 2019)
The purpose of the study was to unveil the reading and writing skills of the students of the English Mention Foreign Language Education Program (ILE) of the UNEFM Municipal Carirubana, Falcón state, Venezuela. It was framed within the qualitative paradigm, with a simple case study design because it worked with a single scenario. The key informants were six (06) students of the IEF Program of the Municipalized UNEFM, from the I-2018 period. To thoroughly understand the study scenario and its problem, the in-depth interview technique was used. The analysis of the information was carried out with the support of the Atlas Ti 6.0 software, from which the codes were extracted and structured in semantic networks, revealing that the lack of a broad vocabulary, deficiencies in cohesion and coherence, coupled with the demotivation of the Students significantly limit the construction of knowledge in this area and the development of their language skills.